2022
DOI: 10.3389/fbioe.2022.946261
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction disruption through activation of the PI3K/AKT pathways in the skin contributes to blister fluid formation after severe tibial plateau fracture

Abstract: Background: Acute compartment syndrome (ACS) is an orthopedic emergency that commonly occurs after severe tibial plateau fracture. Fracture blisters form on the skin, and it was found in our previous study that when blisters form, the compartment pressure significantly decreases. However, the potential mechanism underlying this pressure decrease has not yet been elucidated.Methods: To obtain a comprehensive understanding of the changes that occur after blister formation on the skin, the changes in tight juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Acute Compartment Syndrome (ACS) is an orthopedic emergency that commonly occurs when a severe lower limb fracture causes increased pressure within a muscle compartment that compromises the surrounding tissue. Fracture blisters (FBs) typically form in conjunction with ACS, and Guo ( 1 ) previously found that the formation of blisters results in a significant decrease in compartment pressure. However, the mechanism of FBs formation underlying this decrease in pressure has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Acute Compartment Syndrome (ACS) is an orthopedic emergency that commonly occurs when a severe lower limb fracture causes increased pressure within a muscle compartment that compromises the surrounding tissue. Fracture blisters (FBs) typically form in conjunction with ACS, and Guo ( 1 ) previously found that the formation of blisters results in a significant decrease in compartment pressure. However, the mechanism of FBs formation underlying this decrease in pressure has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with severe traumatic fractures have been reported to have clinically abnormal coagulation functions such as hypercoagulability and hyperfibrinolysis, leading to adverse reactions including venous thrombosis and gastrointestinal bleeding [5,6]. These conditions not only affect the surgical treatment of patients, but also are extremely detrimental to their postoperative recovery [7,8]. Therefore, how to effectively control the postoperative bleeding volume and improve coagulation functions in patients with severe traumatic fractures is an important issue that needs to be addressed in the clinical treatment and postoperative recovery of these patients.…”
Section: Introductionmentioning
confidence: 99%